Trends in the use of natural antioxidants in active food packaging: a review - Sanches-Silva, A. (2015)
The demand for natural antioxidant active packaging is increasing due to its unquestionable advantages compared with the addition of antioxidants directly to the food. Therefore, the search for antioxidants perceived as natural, namely those that naturally occur in herbs and spices, is a field attracting great interest. In line with this, in the last few years, natural antioxidants such as α-tocopherol, caffeic acid, catechin, quercetin, carvacrol and plant extracts (e.g. rosemary extract) have been incorporated into food packaging. On the other hand, consumers and the food industry are also interested in active biodegradable/compostable packaging and edible films to reduce environmental impact, minimise food loss and minimise contaminants from industrial production and reutilisation by-products. The present review focuses on the natural antioxidants already applied in active food packaging, and it reviews the methods used to determine the oxidation protection effect of antioxidant active films and the methods used to quantify natural antioxidants in food matrices or food simulants. Lastly consumers' demands and industry trends are also addressed.